2018
DOI: 10.1002/ecs2.2157
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity patterns in Himalayan forests reveal evidence for environmental filtering of distinct lineages

Abstract: Abstract. Large-scale environmental gradients have been invaluable for unraveling the processes shaping the evolution and maintenance of biodiversity. Environmental gradients provide a natural setting to test theories about species diversity and distributions within a landscape with changing biotic and abiotic interactions. Elevational gradients are particularly useful because they often encompass a large climatic range within a small geographical extent. Here, we analyzed tree communities in plots located thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 74 publications
(140 reference statements)
1
23
0
Order By: Relevance
“…5). By contrast, Shooner et al (2018) found a weak tendency for trees sampled on 500-to 5000-m 2 plots in Arunachal Pradesh to be more phylogenetically clustered at low elevations. Seemingly contradicting this finding, fieldwork in the eastern Himalaya has shown that in small plots, herbs peak at the point where shrubs decline (Bhatta et al 2018); we also found that the decline in herbs shallows at this point (Fig.…”
Section: Climate and Competitionmentioning
confidence: 73%
See 2 more Smart Citations
“…5). By contrast, Shooner et al (2018) found a weak tendency for trees sampled on 500-to 5000-m 2 plots in Arunachal Pradesh to be more phylogenetically clustered at low elevations. Seemingly contradicting this finding, fieldwork in the eastern Himalaya has shown that in small plots, herbs peak at the point where shrubs decline (Bhatta et al 2018); we also found that the decline in herbs shallows at this point (Fig.…”
Section: Climate and Competitionmentioning
confidence: 73%
“…Yan et al (2013) presented an analysis of the adjacent Qinghai-Tibetan Plateau, most of which lies above 4000 m, but they included a section adjacent to northeast India that extends below 1000 m. They found a general increase in clustering with elevation, but at a slower rate at mid-elevations. By contrast, Shooner et al (2018) found a weak tendency for trees sampled on 500-to 5000-m 2 plots in Arunachal Pradesh to be more phylogenetically clustered at low elevations. Our findings may reconcile these observations because we show clustering does not monotonically increase from the lowest to highest elevations.…”
Section: Climate and Competitionmentioning
confidence: 73%
See 1 more Smart Citation
“…As far as we are aware, the extension proposed in this work is the most general in literature, because other similar propositions that seek to expand the Legendre and De Cáceres framework lack some important characteristics presented in the original proposition. Shooner et al (2018) proposed a phylogenetic informed LCBD (also called PLCBD) by using a phylogenetic distance matrix containing PhyloSor values (Bryant et al 2008) for calculating phylogenetic local contribution of sites. Because the use of a phylogenetic distance matrix among sites only allows BD to be decomposed into the local contribution component, it is not possible to obtain the portion of BD that accounts for species contribution to the total variation of the metacommunity (SCBD component).…”
Section: Discussionmentioning
confidence: 99%
“…The zero order of phylogenetic Hill diversity of the two areas is similar (Figure ). This finding may be due to the intensive grazing history, or the unfavorable climate conditions of the areas—the presence of strong environmental filtering in two landscapes leads to similar phylogenetic community composition (Shooner et al, ). In short‐term, EFPM howsoever could not lead to the improvement of plant phylogenetic richness.…”
Section: Discussionmentioning
confidence: 99%